Management Strategies for Recurrent Endometrial Cancer. Issue 9 (2nd September 2018) - Connor, Elizabeth V.; Rose, Peter G.
ABSTRACT: Introduction : Endometrial cancer is the most common gynecologic malignancy in the developed world, and its incidence is increasing. Mortality from this cancer has not improved in recent decades and is primarily driven by high-grade carcinomas that are more likely to present at an advanced stage and ultimately are more likely to recur. The prognosis for recurrent endometrial cancer is poor, especially for the 50% of these women that present with extrapelvic disease recurrence. As a standard of care, recurrent disease has been treated with platinum-based chemotherapy; however, new therapies are emerging as we identify drivers of proliferation and metastasis at the cellular and molecular levels. Areas Covered : We review currently available data for the management of recurrent endometrial cancer, with a focus on systemic treatment of recurrent disease. We discuss the available evidence for first-line, second-line, and subsequent systemic therapy and discuss emerging therapeutic targets including their biologic plausibility and early clinical data. Expert Commentary : Endometrial cancer, though prevalent, remains underfunded and understudied. Recurrent and metastatic disease remains difficult to treat, and prospective randomized data are limited. Our ability to reduce mortality due to this cancer is dependent on identifying new and effective therapeutic strategies for recurrent disease.